PENGARUH DIRECT MARKETING TERHADAP KEPUTUSAN PEMBELIAN KAMAR DI HOTEL GRAND ROCKY BUKITTINGGI - Junaidi, Novrial; Waryono, Waryono; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
This purpose of research is to see how big the influence of variable Direct Marketing (X) to Purchasing Decision at Grand Rocky Hotel Bukittinggi. The sample in this research were 97 people taken using the thechnique of sampling purposive sampling. The data collection was done with the questionnaire using scale likert that they are highly capable validity and reliability. This research result indicate that (1) the Direct Marketing in good category (78%), (2) the Purchasing Decision in good category (87%), (3) the Direct Marketing affect Purchasing Decision of 15,2% and 84,8% influenced by other factors. Then obtained regression coefficient value of 0,338 with a value of t 4,122 on sig. 0,000 < 0,05. This mean that each increase of 1 unit Direct Marketing will increase 0,338 unit of Customer DecisionKeywords: Direct Marketing, Purchasing Decision